Introduction to advertising y promotion: an integrated marketing communications perspectives. - Belch, George E.; Belch, Michael A. (Chicago: Irwin, 1995)
Contents: An introduction to advertising and promotion, the role of advertising and promotion in the marketing process, organizing for advertising and promotion, the role of ad agencies and other marketing communication organizations , perspectives on consumer behavior, markewt segmentation and positioning, the communications process, source message, and channel factors, determining advertising and promotional objetives, the advertising and promotions budget...
Glosary of advertising and promotion terms.
Keywords: Publicidad - Estrategias